The influence of passive heat maintenance on lower body power output and repeated sprint performance in professional rugby league players - Kilduff, L. P.; West, D. J.; Williams, N.; Cook, C. J. (Journal of Science and Medicine in Sport, 2013)
Objectives: The pre-competition warm-up mediates many temperature related physiological changes which generally lead to an improvement in performance. However, after ceasing exercise body temperature declines rapidly, which reduces some of the benefits of the initial warm-up. We examined the effects of a passive heat maintenance strategy on post-warm-up core temperature (Tcore) and performance in professional rugby league players. Design: Twenty professional rugby league players completed this randomised and counter-balanced study. Methods: After a standardised warm-up, players completed a countermovement jump (CMJ) before resting for 15 min wearing normal training attire (control) or wearing a passive heat maintenance jacket (PHM), players then completed another CMJ and a repeated sprint protocol (RSA). Tcore was measured at baseline, post-warm-up, pre-RSA and post-RSA. CMJ were analysed for peak power output (PPO), and RSA for fastest, mean and total sprint time. Results: Post-warm-up Tcore (mean ± SD; control 37.70 ± 0.28; PHM 37.70 ± 0.27 °C; p = 0.741) and PPO (control 5220 ± 353 vs. PHM 5213 ± 331 W; p = 0.686) were similar between conditions. At pre-RSA, PHM was associated with greater Tcore (control 37.14 ± 0.31 vs. PHM 37.51 ± 0.30 °C; p < 0.001) and PPO (control 4868 ± 345 vs. PHM 5056 ± 344 W; p < 0.001) when compared to control. The decline in PPO from post-warm-up to pre-RSA was related to the drop in Tcore (r = 0.71; p < 0.001). During the RSA, fastest, mean and total sprint time were all improved under PHM compared to control (p < 0.05). Conclusions: Passive heat maintenance is an effective method of attenuating the post-warm-up decline in Tcore and improves PPO and repeated sprint ability in professional rugby league players.